Giant Saman [sic] Tree, Queen's Park, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Waterman, Trinidad, 2010)
The postcard shows a tram car passing a Samaan tree located in the Queen's Park Savannah in Port of Spain. Located at back of the postcard, to the bottom, are the words 1019 "Par excellence".
Colour: Coloured (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Savannas--Trinidad and Tobago; Albizia; Cities and towns--Trinidad and Tobago--Port of Spain; Queen's Park Savannah